An increase in canopy cover leads to masting in Quercus ilex - Camarero, J. Julio; Albuixech, Jorge; López-Lozano, Raúl; Casterad, M. Auxiliadora; Montserrat-Martí, Gabriel (Trees, 2010)
Masting is the intermittent and synchronous production of large crops, but its relation to tree growth remains elusive despite the ecological relevance of mast seeding. The production of huge fruit crops has been linked to the accumulation and consumption of resources as nutrients and carbohydrates, but no conclusive assessment has supported this assumption. To evaluate if masting takes place once trees’ canopies reach maximum foliage, changes in canopy cover were measured in Quercus ilex susbp. ballota stands before and after a masting event using the normalized difference vegetation index (NDVI). The results on the whole underline that masting in Q. ilex occurred once maximum levels of NDVI and canopy cover were reached. After the masting event, NDVI dropped, leaf shedding increased and trees produced shorter shoots, narrower tree rings and fewer acorns than before the masting event. These ﬁndings support our contention that an increase in canopy cover precedes masting.
Keywords: acorn; canopy cover; Mast seeding; quercus ilex subsp. ballota; Remote sensing